2B or not to be – The 45-year saga of the Montreal Platelet Syndrome - Poon, Man-Chiu; Rand, Margaret L.; Jackson, Shannon C. (Thrombosis and Haemostasis, 2010)
Over 45 years ago, Montreal Platelet Syndrome was first described as a rare inherited platelet disorder characterised by macrothrombocytopenia with spontaneous platelet clumping, abnormal platelet shape change upon stimulation and a defect in platelet calpain. This syndrome has now been reclassified as type 2B von Willebrand disease with the V1316M VWF mutation in the only kindred ever reported. We herein revisit the historical platelet characteristics originally described in Montreal Platelet Syndrome in light of the new diagnosis. This paper will review the 45-year saga of Montreal Platelet Syndrome, a story that highlights the value of revisiting a rare diagnosis to look for a more common explanation.
Keywords: Von Willebrand factor; Von Willebrand disease; Platelet pathology / inherited and acquired; Thrombocytopenia; Inherited coagulation disorders